Multiple tracheobronchial diverticula in a post‐TB patient: A case report. Issue 12 (27th December 2022) - Timilsina, Bibek; Pangeni, Raju Prasad; Khadka, Sulochana; Regmi, Pradeep Raj; Dhakal, Binaya
Abstract: The presence of multiple tracheal and bronchial diverticula is a rare condition. We present a case of a 22‐years old non‐smoker male with a history of pulmonary tuberculosis, having multiple tracheal and bronchial diverticula along with other common sequelae such as stenosed and collapsed upper lobe bronchi. Abstract : Tracheobronchial diverticulosis is a uncommon entity in a young non‐smoking population. The presence of extensive bronchial diverticula along with sequelae of endobronchial tuberculosis in this patient poses a diagnostic and therapeutic challenge in a resource limited setting.